The real estate investor's answer book : - Cummings, Jack (McGraw-Hill, 2006)
Whether you own a dozen apartment buildings or are contemplating your first real estate deal, this is the one book that will answer all your questions. Sinking money into land, a house, a vacation home, or a rental unit can be one of the most stressful events in a person's life-especially if you're counting on that property to produce cash flow and equity build-up. Author and real estate pro Jack Cummings knows the answers-and delivers 30 years of insider information, addressing questions on more than 200 potential real estate pitfalls, including: How can I predict property value changes before anyone else? What hidden values should I look for in a rental property? How do I get the most out of a real estate agent? What's the secret to dealing with tax issues? How do I know how much rent I should ask for my rental property? What's the most important thing to know before buying a vacation property?